2006
DOI: 10.1002/humu.20281
|View full text |Cite
|
Sign up to set email alerts
|

Different genetic pathways in the development of periocular sebaceous gland carcinomas in presumptive Muir-Torre syndrome patients

Abstract: Periocular sebaceous gland carcinomas (SGCs) occur in the eyelids either sporadically or as a phenotypic feature of Muir-Torre syndrome (MTS). In knockout mice mismatch-repair (MMR) defects or inactivation of the fragile histidine triad (FHIT) gene are associated with MTS-like signs, including SGC. To dissect the genetic alterations associated with microsatellite instability (MSI) and inactivation of the FHIT gene, we studied nine periocular SGC specimens from MTS patients. Immunohistochemistry was performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
2
24
0
6
Order By: Relevance
“…Recent reports from our laboratory have established a role for Fhit loss in the initiation of genome instability [2224, 32], and have unambiguously characterized Fhit as a ‘genome caretaker’, a role intimated by the discovery that Fhit knockout mice develop sebaceous tumors [10], similar to those caused by loss of DNA mismatch repair enzymes [33]. Such sebaceous carcinomas in humans can also be caused either by loss of Fhit or loss of mismatch repair enzymes [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from our laboratory have established a role for Fhit loss in the initiation of genome instability [2224, 32], and have unambiguously characterized Fhit as a ‘genome caretaker’, a role intimated by the discovery that Fhit knockout mice develop sebaceous tumors [10], similar to those caused by loss of DNA mismatch repair enzymes [33]. Such sebaceous carcinomas in humans can also be caused either by loss of Fhit or loss of mismatch repair enzymes [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…It is well established that a subset of sebaceous lesions harbor microsatellite instability and mutations in proteins encoding DNA mismatch repair enzymes 8, 11, 12, 35, 36. However, the presence of mismatch repair deficiency has been shown to occur less frequently in carcinomas than in benign sebaceous lesions and is seen more commonly in tumors occurring outside of the head and neck region 11, 12.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study specifically examined periocular sebaceous carcinomas in patients with concurrent visceral malignancy (a Muir-Torre syndrome phenotype) and found that the fragile histadine triad gene ( FHIT ) was disrupted in a subset of cases with confirmed microsatellite stability 35. The authors suggested that mutations in FHIT provided another mechanism for sebaceous carcinoma formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to remember that an MSH6 defect was once thought to occur only in association with an MSH2 defect but has since been shown to occur independently 30. Goldberg et al 31 have described microsatellite-stable MTS associated with inactivation of the fragile histidine triad gene. However, they were unable to show a germline defect linking the sebaceous gland carcinoma and the visceral malignancy.…”
Section: Discussionmentioning
confidence: 99%